Kendala Orang Tua Dalam Mendampingi Anak Belajar Pada Masa Covid 19 Di Kota Serang - Imas Mastoah; Zulaela MS (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
The purpose of the results of this study is to find out more about the problems felt by parents when accompanying children to study at home. Related to the purpose of this study, the effective way of researchers using this type of research is descriptive qualitative type, through interview techniques followed by reducing data and conclusions. In extracting data from this study the researcher was able to produce and show a general picture experienced by parents (respondents) in accompanying children who were unable to study at home during the Covid-19 period, this was extraordinary by draining high anger appetite in a fairly frequent time span. , quota limitations, even parents, especially mothers, are very complaining about the learning given virtually (youtube,) and the results of the provided material such as the Google Class Room followed by evaluations and assignments, this is what raises the anxiety of parents at all. do not understand the material being taught that is delivered via virtual, especially mathematics in grade VI. This needs to be examined together when the current emergency condition is requested for policy makers so that educators, especially for elementary school children, with learning at home do not focus on heavy tasks. This has resulted in the anxiety and confusion of parents whose education cannot be equated with today's world, where it is very difficult to use technology (learning media) such as using Android phones, gadgets. With this research, the researcher tries to make a valuable contribution to further research in exploring the various obstacles faced by parents Keywords: learning; covid-19; parents, obstacles References A. Tabi’in. (2020). Problematika Stay At Home Pada Anak Usia Dini Di Tengah Pandemi Covid 19. Jurnal Golden Age, 4(01), 191–200. Al Amin, M. N. K. (2020). Menakar Nilai Kemanfaatan Penangguhan Walimat Al-‘Ursy Di Masa Darurat COVID-19 Melalui Analisis Sadd Adz-Dzari’ah. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 10(1), 27–38. Anugrahana, A. (2020). Hambatan, Solusi dan Harapan: Pembelajaran Daring Selama Masa Pandemi Covid-19 Oleh Guru Sekolah Dasar. Scholaria: Jurnal Pendidikan dan Kebudayaan, 10(3), 282–289. Arsyad, A. (2017). Media Pembelajaran, Edisi Revisi. Rajawali Pers. Astuti, D., Rivaie, W., & Ibrahim, Y. (2013). Analisis Peran Orang Tua Dalam Meningkatkan Hasil Belajar Siswa Kelas X SMK Muhammadiyah Pontianak. Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2(6). Cahyati, N., & Kusumah, R. (2020). Peran Orang Tua Dalam Menerapkan Pembelajaran Di Rumah Saat Pandemi Covid 19. Jurnal Golden Age, 04(1), 152–159. Emiyati, A. (2020). Kendala Orang Tua Mendampingi Anak Belajar di Rumah Dalam Menghadapi Situasi Covid 19. Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 4(1), 8–16. Hidayat, F. (2016). PENGASUHAN ANAK USIA DINI DALAM PERSPEKTIF PSIKOLOGI. PROSIDING SEMINAR NASIONAL PERAN PENGASUHAN ANAK RAUDHATUL ATFAL DALAM MEMBANGUN KARAKTER BANGSA, 1–4. Hidayat, F., & Imroatun, I. (2018). Keluarga Berencana Dan Pengasuhan Anak Usia Dini Di Indonesia Perspektif Psikologi. International Conference Proceeding Konsepsi dan Implementasi Pendidikan Islam Anak Usia Dini Book two, 164–171. Huliyah, M. (2016). Hakikat Pendidikan Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71. Imroatun, I. (2014). Permainan Tradisional Sebagai Pembelajaran Kecakapan Sosial Bagi Anak Usia Dini. Jurnal Sains Psikologi, 3(1), 1–11. Kompas.com. (2020). PSBB Banten Diperpanjang Lagi. Kompas.com. Moleong, L. J. (2017). Metodologi Penelitian Kualitatif (Bandung). Rosdakarya. Musfiroh, T. (n.d.). Bermain Sambil Belajar dan Mengasah Kecerdasan. Depdiknas. Pandoman, A. (2020). Analisis Quietus Politik Terhadap Upaya Pemerintah Menangani Wabah Covid-19 Pasca Deklarasi Public Health Emergency Of International Concern (PHEIC). Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 10(1), 1–12. https://doi.org/10.47200/ulumuddin.v10i1.379 Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 9(1), 49–60. Purandina, I. P. Y., & Winaya, I. M. A. (2020). Pendidikan Karakter di Lingkungan Keluarga Selama Pembelajaran Jarak Jauh pada Masa Pandemi COVID-19. Cetta: Jurnal Ilmu Pendidikan, 3(2), 270–290. Rahman Riyanda, A., Herlina, K., & Anggit Wicaksono, B. (2020). Evaluasi Implementasi Sistem Pembelajaran Daring Fakultas Keguruan Dan Ilmu Pendidikan Universitas Lampung. IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 4(1), 66–71. Rohayani, F. (2020). Menjawab Problematika Yang Dihadapi Anak Usia Dini di Masa Pandemi COVID-19. Qawwam: Journal For Gender Mainstreaming, 14(1), 29–50. Santoso, F. S. (2020). Masa Depan Pendidikan Hukum Islam Di Perguruan Tinggi Keagamaan Islam Refleksi Pembelajaran Di Masa Kedaruratan COVID-19. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 10(1), 13–26. https://doi.org/10.47200/ulumuddin.v10i1.378 Sevima.com. (2020). 6 Metode Pembelajaran Paling Efektif di Masa Pandemi Menurut Para Pakar. Wardani, A., & Ayriza, Y. (2021). Analisis Kendala Orang Tua dalam Mendampingi Anak Belajar di Rumah Pada Masa Pandemi Covid-19. Jurnal Pendidikan Anak Usia Dini, 5(1), 772–782.